The study of the psychological aspects of the phenomenon of «Faith» in the context of sports activities of representatives of various sports fields - Ashkinazi S.M.; Sytnik G.V.; Andreev Vit.V.; Andreev V.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study – analysis of the psychological roots of the phenomenon of faith, the definition of its role and the demonstration of ways to implement it in the daily lives of students involved in sports. Methods and structure of the study. In order to identify the peculiarities of the perception of the phenomenon of "Faith" among student-athletes, their views on faith as such, their need for it, their belief in the existence of God, the depth of religious beliefs, predisposition to superstition, participation in religious rituals and attitudes towards paranormal phenomena were analyzed. The study involved 78 fifth-year students of various specializations from the P.F. Lesgaft National University in St. Petersburg. All participants were athletes. Results and conclusions. Faith as a phenomenon reflects the diversity of aspects of mental reality. It has been established that the need for faith is activated under the influence of specific life events, especially often it occurs during periods of crisis. During the study of the phenomenon of faith, four main categories were identified for analysis: "spirituality" (34.29%), "transpersonal aspect" (10.48%), "sphere of extra-psychic phenomena" (7.62%) and "area of psychic phenomena" (47.62%). The presented classification gives grounds to assert that faith is primarily a mental construct. The key concept used to describe faith is "spirituality." Faith has an effect on an individual, manifesting itself in support, inspiring optimism, accompanying them through life, and having an overall beneficial effect. It is important to perceive faith as an integral part of a psychological portrait that unites various aspects of the psyche into a single whole. Such integration contributes to a fuller understanding of the importance of faith in human life and its impact on the psychological aspects of existence. Considering faith from this point of view allows us to see it as a powerful factor shaping personality and determining behavior. The positive influence of faith can manifest itself in a wide variety of areas of life, from interpersonal relationships to professional activities. Faith is able to give meaning to life, help to cope with difficulties and find a way out of difficult situations.